Curcumin and Intestinal Oxidative Stress of Pigs With Intrauterine Growth Retardation: A Review - Tang, Xiaopeng; Xiong, Kangning; Wassie, Teketay; Wu, Xin (Frontiers in Nutrition, 2022)
Intrauterine growth restriction (IUGR) refers to the slow growth and development of a mammalian embryo/fetus or fetal organs during pregnancy, which is popular in swine production and causes considerable economic losses. Nutritional strategies have been reported to improve the health status and growth performance of IUGR piglets, among which dietary curcumin supplementation is an efficient alternative. Curcumin is a natural lipophilic polyphenol derived from the rhizome of Curcuma longa with many biological activities. It has been demonstrated that curcumin promotes intestinal development and alleviates intestinal oxidative damage. However, due to its low bioavailability caused by poor solubility, chemical instability, and rapid degradation, the application of curcumin in animal production is rare. In this manuscript, the structural-activity relationship to enhance the bioavailability, and the nutritional effects of curcumin on intestinal health from the aspect of protecting piglets from IUGR associated intestinal oxidative damage were summarized to provide new insight into the application of curcumin in animal production.